Penerapan Model Evaluasi untuk Meningkatkan Kualitas Pelaksanaan Praktikum Fisika Dasar pada Mahasiswa Fmipa Unima: Penelitian - Rondonuwu, Anneke Tienneke (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to examine the effectiveness of implementing an evaluation model as an assessment instrument for learning outcomes while simultaneously improving the quality of laboratory activities in the Basic Physics course. The research participants were 38 undergraduate students of the Faculty of Mathematics and Natural Sciences (FMIPA) enrolled in Class B of the Basic Physics course during the first semester. The study employed a classroom action research design conducted through systematic and iterative stages. Data were collected through observation, documentation, and performance-based laboratory assessments, and subsequently analyzed using a combination of qualitative and quantitative approaches. The findings indicate a measurable improvement in the quality of laboratory implementation across all phases of the practicum. In the preparation phase, student performance increased to 68.5%, encompassing the ability to formulate research problems, articulate practicum objectives, demonstrate understanding of underlying theoretical concepts, and construct appropriate data tables. The implementation phase showed an improvement of 72.5%, reflected in students’ proficiency in selecting and assembling laboratory equipment, accurately manipulating instruments, reading measurement scales, and demonstrating scientific attitudes such as discipline, responsibility, active participation, and collaboration within groups. In addition, students’ collaborative skills—particularly initiative, leadership, and engagement in group work—exhibited notable development. The reporting phase achieved an improvement rate of 71.5%, as evidenced by accurate data presentation, correct application of measurement units, repeated measurements, appropriate use of formulas in data analysis, graphical representation of results, and the ability to draw logical conclusions supported by interpretation and acknowledgment of limitations. Overall, the results suggest that the systematic application of an evaluation model effectively enhances both the process and outcomes of Basic Physics laboratory activities, particularly in terms of students’ practical skills, scientific attitudes, and analytical competencies.